Перші відомості про іржасті гриби Національного природного парку "Синевир" - Тихоненко, Ю.Я.; Дудка, І.О. (Український ботанічний журнал, 2014)
В результате микологических обследований в Национальном природном парке «Синевир» в июне—августе 2013 г. было выявлено 25 видов из 6 родов порядка Pucciniales (Puccinia Pers. — 13 видов, Phragmidium Link — 5, Melampsora Castagne — 4 и по одному виду из родов Coleosporium Lév., Gymnosporangium R. Hedw. ex DC. и Uromyces (Link) Unger). Рабо а иллюстрирована 6 микрофотографиями. The first mycological study of the National Nature Park “Synevyr” (west Ukraine) in June — August 2010 reveals 25 species of 6 genera of the order Pucciniales. The following genera are represented by: Puccinia Pers. — 13 species, Phragmidium Link — five, Melampsora Castagne — four, Coleosporium Lév., Gymnosporangium R. Hedw. ex DC. and Uromyces (Link) Unger — one species each. The article is illustrated by 6 microphotographs.